Identifikasi Bakteri Escherichia coli dan Salmonella sp. pada Produk Ayam Geprek di Kantin Universitas Tadulako - Rofiqoh, Rofiqoh; Kundera, I Nengah; Windarsih, Yulia; Buntu, Amalia; Budiarsa, I Made; Ashari, Abdul (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify the presence of Escherichia coli and Salmonella sp. in